Updating studies of past life and ancient ecologies using defossilized organismal proxies - Johnson, Erynn; Peterman, David; Carter, Aja (Frontiers in Earth Science, 2022)
The fossil record represents the world’s largest historical dataset of biodiversity. However, biomechanical and ecological the potential of this dataset has been restricted by various unique barriers obstructing experimental study. Fossils are often partial, modified by taphonomy, or lacking modern analogs. In the past, these barriers confined many studies to descriptive and observational techniques. Fortunately, advances in computer modeling, virtual simulations, model fabrication, and physical experimentation now allow ancient organisms and their biomechanics to be studied like never before using “Defossilized Organismal Proxies” (DOPs). Although DOPs are forging new approaches integrating ecology, evolutionary biology, and bioinspired engineering, their application has yet to be identified as a unique, independent methodological approach. We believe that techniques involving DOPs will continue revolutionizing paleontology and how other related fields interact with and draw insights from life’s evolutionary history. As the field of paleontology moves forward, identifying the framework for this novel methodological development is essential to establishing best practices that maximize the scientific impact of DOP-based experiments. In this perspective, we reflect on current literature innovating the field using DOPs and establish a workflow explaining the processes of model formulation, construction, and validation. Furthermore, we present the application of DOP-based techniques for non-specialists and specialists alike. Accelerating technological advances and experimental approaches present a host of new opportunities to study extinct organisms. This expanding frontier of paleontological research will provide a more holistic view of ecology, evolution, and natural selection by breathing new life into the fossil record.